Multiple Drug Resistance Pattern in Urinary Tract Infection Patients in Saudi Arabia - Ahmad, Shamweel (Bangladesh Journal of Infectious Diseases, 2019)
Background: Urinary tract infection (UTI) is the most common problem in hospitalized and outdoor patients. It is mainly found in females because of the shortness of the urethra and closeness to anus, which facilitate entrance of fecal micro–flora to urinary tract. Knowledge of local antimicrobial resistance patterns is essential for evidence- based empirical antibiotic prescribing. Objective: The main aim of this study was to analyze the drug resistance pattern of bacterial isolates from suspected urinary tract infection (UTI) patients in Al-Kharj, Saudi Arabia. Methodology: This cross- sectional study was carried out in Al-Kharj region of Saudi Arabia from 1st. September, 2016 to 28th. February, 2017. Midstream urine specimens were collected from patients at a general hospital. The specimens were cultured and the isolates were identified using standard microbiological techniques. The antibiotic susceptibilities of the isolates were also determined. Results: The number of patients with urinary tract infection who yielded positive cultures from their mid stream urine specimens was 249(12.0%) out of 2064 specimens. The commonest isolates were Escherichia coli (53.4%) and Klebsiella pneumoniae (28.5%). Other bacterial pathogens were Proteus mirabilis (5.2%), Pseudomonas aeruginosa (4.4%), Streptococcus agalactiae (6.0%) and Enterococcus faecalis. (2.5%). Conclusions: E. coli is the most common causative agent of urinary tract infection followed by Klebsiella pneumoniae. Ampicillin, Augmentin, Cotrimoxazole, Norfloxacin and Nalidixic acid have the highest resistance rates against both these pathogens. No isolate is found to be resistant to imipenem. Bangladesh Journal of Infectious Diseases 2019;6(1):3-7